Review of the epidemiology of burn injuries in Ethiopia; implications for study design and prevention - Edna Ogada (Burns Open, 2019)
BackgroundMajority of burn deaths occur in lower and middle income countries where there are limited prevention interventions. Planning and resource allocation for prevention requires consistent and reliable data but published data from these settings are limited in scope and rigor and often not replicable.ObjectiveThe objective of the review was; to examine the literature to determine what information exists on the epidemiology of burn injuries in Ethiopia; to assess its utility for planning interventions for burn prevention.MethodsA broad key term search was performed in Safety Lit and MEDLINE. We reviewed the literature on burn epidemiology in Ethiopia, to assess its utility for planning interventions for burn prevention.ResultsOur search strategy yielded more information than burn specific search strategies. We identified 23 studies drawn from observational and primarily hospital-based, cross sectional studies. They offer preliminary evidence for recommendations for future surveillance, risk factor exploration and prevention initiatives.ConclusionWe conclude that the low rate of burn cases identified from observational studies; the challenge of defining and coding injury in the field; recall bias; mean case series data from hospital data are more efficient and sustainable for monitoring burn epidemiology in Ethiopia. We recommend the establishment of a national trauma registry or WHO’s Global Burn Registry (GBR) to gather data in Ethiopia and countries in comparable settings. Community studies, provide the best avenue to gauge knowledge, attitudes and practices relevant to injury prevention, first aid and health seeking behaviour and to move from research to action that takes the local context into account. This critical preliminary synthesis on burn epidemiology frames future national research and policy on burn surveillance and prevention.